1999
DOI: 10.1007/s00585-999-1293-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes of the first Schumann resonance frequency during relativistic solar proton precipitation in the 6 November 1997 event

Abstract: Abstract. The variations of the ®rst mode of Schumann resonance are analyzed using data from Kola peninsula stations during the solar proton event of 6 November 1997. On this day the intensive¯ux of energetic protons on GOES-8 and the 10% increase of the count rate of the neutron monitor in Apatity between 1220 and 2000 UT were preceded by a solar X-ray burst at 1155 UT. This burst was accompanied by a simultaneous increase of the Schumann frequency by 3.5%, and the relativistic proton¯ux increase was accompan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 8 publications
1
11
0
Order By: Relevance
“…The changes of ionosphere conductivity are manifested ambiguously in indices for different types of geophysical disturbances. The results of the frequency analysis with 5 min resolution, given here and in [ Roldugin et al , 1999, 2001, 2003], yield somewhat unexpected result: during a solar X‐ray burst the SR frequency increases, however after the following energetic proton precipitation it decreases.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The changes of ionosphere conductivity are manifested ambiguously in indices for different types of geophysical disturbances. The results of the frequency analysis with 5 min resolution, given here and in [ Roldugin et al , 1999, 2001, 2003], yield somewhat unexpected result: during a solar X‐ray burst the SR frequency increases, however after the following energetic proton precipitation it decreases.…”
Section: Discussionmentioning
confidence: 76%
“…Variations in the first mode SR frequency during SPEs were studied by Roldugin et al [1999, 2001, 2003] who compared the SR frequency averaged over 5 min with the 5 min data on the proton fluxes and X‐ray intensity measured onboard the GOES satellite. The first mode SR frequency appeared to decrease by about 0.2–0.4 Hz during the main phase of the energetic proton precipitation lasting for several hours.…”
Section: Introductionmentioning
confidence: 99%
“… Roldugin et al [1999, 2001] observed not an increase but a decrease of the frequency during SPE. They have considered 5‐min values of the first SR frequency and >100 MeV solar proton intensity, the duration of the events being several hours only.…”
Section: Introductionmentioning
confidence: 87%
“… Cannon and Rycroft [1982] found fluctuations of the SR frequency during sudden ionospheric disturbances. Roldugin et al [1999, 2001] report that very intensive solar X‐ray bursts, preceding the proton flares, give rise to the increase of the resonance frequency.…”
Section: Introductionmentioning
confidence: 99%
“…These two effects produce opposite actions on the Schumann resonances: the increase in the conductivity implies a decrease in the resonance frequencies, but the lower value for the ionosphere altitude produces higher values for these frequencies. Therefore depending on the particular modification of the conductivity and ionosphere altitude, a solar proton event may cause an increase [ Schegel and Füllekrug , 1999] or a decrease [ Roldugin et al , 1999, 2001] in the first Schumann resonance.…”
Section: Tlm Numerical Model For Earthmentioning
confidence: 99%